THE ROLE OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN SCIENCE, EDUCATION, AND INDUSTRY (Uzbekistan Open Conference, 2026)
This article examines the systemic impact of digital transformation and artificial intelligence (AI) technologies on key spheres of human activity. It analyzes statistical indicators of AI integration into the global economy and explores transformations in research methodologies, educational paradigms, and production cycles within Industry 4.0.